2016
DOI: 10.1186/s12866-016-0898-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the fecal microbiota of healthy Japanese adults reveals a new bacterial lineage associated with a phenotype characterized by a high frequency of bowel movements and a lean body type

Abstract: BackgroundIn Japan, a variety of traditional dietary habits and daily routines have developed in many regions. The effects of these behaviors, and the regional differences in the composition of the gut microbiota, are yet to be sufficiently studied. To characterize the Japanese gut microbiota and identify the factors shaping its composition, we conducted 16S metagenomics analysis of fecal samples collected from healthy Japanese adults residing in various regions of Japan. Each participant also completed a 94-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 31 publications
4
81
4
1
Order By: Relevance
“…It also positively correlated with alpha-diversity, which was higher in lean compared to obese subjects in the TwinsUK population. The association of Christensenellaceae with a lean phenotype was also observed in Missouri twins (64), the Dutch LifeLines- DEEP population (17), Koreans (40) and Japanese individuals (51). Christensenellaceae was subsequently linked to visceral fat phenotypes in the TwinsUK cohort (3), as well as with healthy levels of triglycerides in the Dutch LifeLines- DEEP cohort (17).…”
Section: Heritable Taxa Of the Human Gut Microbiome Are Increasingly mentioning
confidence: 75%
See 1 more Smart Citation
“…It also positively correlated with alpha-diversity, which was higher in lean compared to obese subjects in the TwinsUK population. The association of Christensenellaceae with a lean phenotype was also observed in Missouri twins (64), the Dutch LifeLines- DEEP population (17), Koreans (40) and Japanese individuals (51). Christensenellaceae was subsequently linked to visceral fat phenotypes in the TwinsUK cohort (3), as well as with healthy levels of triglycerides in the Dutch LifeLines- DEEP cohort (17).…”
Section: Heritable Taxa Of the Human Gut Microbiome Are Increasingly mentioning
confidence: 75%
“…In addition, this group reported that three OTUs belonging to Christensenellaceae and one OTU classified as Methanobrevibacter positively associated with colonic transit time and with protein degradation products. In accord, in a study of Japanese subjects, the Christensenellaceae family negatively associated with bowel movement frequency (51). With longer transit time, microbiota have longer to work on substrates, liberate additional substrates (which can increase niche space and diversity), and potentially slower growing microbiota have the necessary gut retention time to reach measurable levels, all of which could lead to greater richness.…”
Section: Heritable Taxa Of the Human Gut Microbiome Are Increasingly mentioning
confidence: 98%
“…However, a gut microbiota‐associated predictor in a subgroup of patients was identified: in particular, inactive disease was predicted by a lower relative abundance of Mogibacteriaceae (Firmicutes) for patients with oligoarthritis . Authors discuss that nothing is known about Mogibacteriaceae in the context of autoimmune diseases, whereas this bacterium was less present in obese Japanese subjects, in comparison to lean subjects …”
Section: Role Of Microbiota and Efficacy Of Therapeutics In Jiamentioning
confidence: 98%
“…92 Authors discuss that nothing is known about Mogibacteriaceae in the context of autoimmune diseases, whereas this bacterium was less present in obese Japanese subjects, in comparison to lean subjects. 93 In 18 French adult patients with spondyloarthritis, modifications of the microbiota composition were observed after 3 months of anti-TNF treatment (15 patients received etanercept, 2 received adalimumab, and 1 received infliximab), but no specific taxon was modified, whatever the clinical response. Authors performed an analysis to identify predictors of anti-TNF treatment after 3 months of therapy, selecting two subgroups of patients, five with good response (change in disease activity score > 2), and eight with limited efficacy (change in disease activity score < 1).…”
Section: Microbiota and Jia Susceptibilitymentioning
confidence: 99%
“…Such co-occurrences of taxa across subjects reflect shared environmental preferences, but to determine if they represent metabolic or physical interactions requires further study. The family Christensenellaceae consistently forms the hub of co-occurrence networks with other taxa (6, 8, 9, 18, 19). Notably, gut methanogens (specifically, of the archaeal family Methanobacteriaceae ) are often reported as part of the Christensenellaceae co-occurrence consortium (4, 2022).…”
Section: Introductionmentioning
confidence: 99%